a COMPARATIVE STUDY on the effect of coriandrum sativum , Nigella sativa, and calendula officinalis on the testis of rat - Ja'afer, firdous M.; Haddad, Farad Y.S.; Baker, Hiwa; Hallaji, Numan A.E (Journal of the Faculty of Medicine Baghdad, 2008)
Background:Coriandrum sativum, Nigella sative, and Calendula officinalis are commonly used herbs in traditional medicine.